Visual Identity as a Visual Representation Media in Branding Bakso Atok - Indrajaya, Grandy; Redintan, Muhammad Justin (IMAGIONARY, 2024)
Designing a visual identity is very important because it is an effort to represent and represent a particular brand or brands. Apart from representing the brand, visual identity can also increase consumers' sense of awareness in choosing the brand. This research is interesting in raising the problem of street vendors, namely "meatball atok" which do not yet have a visual identity, namely a logo. Many consumers are doubtful about the food being sold because they feel unsure about the quality and taste image plus they don't have a visual identity for their merchandise, namely a logo. Atok meatballs need ideas and innovation to increase consumer awareness and trust. To solve this problem, designing a visual identity is very important and important because what consumers see first is the brand's logo. The aim of this design is to increase consumer confidence in Atok meatballs and make it easily recognized by the public in a wider scope, therefore the logo design was created through various processes from observation, sketching, determining the layout and choosing colors to digitalization according to the concept needed and desired . And with the logo of Atok meatballs, it can improve the quality of the branding image and the quantity of sales results so that many people have confidence and awareness of Atok meatballs and in developing their business can be used as an example by other traders or MSMEs who are also in the development stage of their business.